Understanding the Natural History of Postoperative Pain and Patient-Reported Opioid Consumption After Elective Spine and Nerve Surgeries With an Automated Text Messaging System. Issue 3 (March 2022) - Punchak, Maria A.; Agarwal, Anish K.; Joshi, Disha; Xiong, Ruiying; Malhotra, Neil R.; Marcotte, Paul J.; Ozturk, Ali; Petrov, Dmitriy; Schuster, James; Welch, William; Delgado, M. Kit; Ali, Zarina
Abstract : BACKGROUND: There is a gap in understanding how to ensure opioid stewardship while managing postoperative neurosurgical pain. OBJECTIVE: To describe self-reported opioid consumption and pain intensity after common neurosurgery procedures gathered using an automated text messaging system. METHODS: A prospective, observational study was performed at a large, urban academic health system in Pennsylvania. Adult patients (≥ 18 years), who underwent surgeries between October 2019 and May 2020, were consented. Data on postoperative pain intensity and patient-reported opioid consumption were collected prospectively for 3 months. We analyzed the association between the quantity of opioids prescribed and consumed. RESULTS: A total of 517 patients were enrolled. The median pain intensity at discharge was 5 out of a maximum of pain score of 10 and was highest after thoracolumbar fusion (median: 6, interquartile range [IQR]: 4-7). During the follow-up period, patients were prescribed a median of 40 tablets of 5-mg oxycodone equivalent pills (IQR: 28-40) and reported taking a median of 28 tablet equivalents (IQR: 17-40). Responders who were opioid-naive vs opioid-tolerant took a similar median number of opioid pills postoperatively (28 [IQR: 17-40] vs 27.5 [17.5-40], respectively). There was a statistically significant positive correlation between the quantity of opioids prescribed and used during the 3-month follow-up (Pearson R = 0.85, 95% CI [0.80-0.89], P < .001). The correlation was stronger among patients who were discharged to a higher level of care. CONCLUSION: Using real-time, patient-centered pain assessment and opioid consumption data will allow for the development of evidence-based opioid prescribing guidelines after spinal and nerve surgery.